West African Migrations Transnational and Global Pathways in a New Century - Okome, M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
Drawing on the interdisciplinary research projects of scholars from various social science and humanities disciplines, this book explores how African migration to Western countries after the neo-liberal economic reforms of the 1980s transformed West African states and their new transnational populations in Western countries.
Keywords: Political sociology; International relations; Africa—Politics and government; Ethnology—Africa.; Sociology; Demography; Political Sociology; International Relations; African Politics; African Culture; Sociology, general; Demography